Liz Lerman's Critical Response Process: A Method for Getting Useful Feedback on Anything you Make, from Dance to Dessert - Lerman, Liz; Borstel, John (Takoma Park, MD Dance Exchange, 2003)
"Liz Lerman's Critical Response Process is a multi-step, group system for giving and receiving useful feedback on creative processes and artistic works-in-progress. This book offers a detailed introduction to the Process, beginning with its three roles and four core steps. "...the best tool we've ever encountered in assisting individual artists at the most vulnerable stages of creation...empowers artists and invests responders with real responsibility as audience members." (James C. Nicola, Artistic Director, New York Theater Workshop)
Keywords: Artistic research; Education